2009
DOI: 10.5897/ajb09.1214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different combinations and concentrations of growth regulators and photoperiod on somatic embryogenesis of cucumis melo var. flexuosus

Abstract: The present study describes the effects of medium, explant type and photoperiod on somatic embryogenesis of snake melon (Cucumis melo var. flexuosus). Two different types of explant (cotyledon and hypocotyls) obtained from 3 days old snake melon seedlings and culture conditions were investigated for somatic embryogenesis. Explants were cultured on Murashige and Skoog (1962) (MS) medium supplemented with 23 different combinations of auxins (2,4-dichlorophenoxyacetic acid, 2,4-D; α-naphthalene acetic acid, NAA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In conclusion, the present study showed that, callus induction and SE were strongly affected by plant growth regulators and culture conditions. The medium containing both auxin and cytokinin at any concentration was capable of inducing the formation of somatic embryogenesis but differences were observed based on the type and concentration of plant growth regulators and light conditions (Nuray et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, the present study showed that, callus induction and SE were strongly affected by plant growth regulators and culture conditions. The medium containing both auxin and cytokinin at any concentration was capable of inducing the formation of somatic embryogenesis but differences were observed based on the type and concentration of plant growth regulators and light conditions (Nuray et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%